Synergy of MSMEs and Food Innovation: Utilization of Raja Nangka Banana Peel Flour in Making Dry Cakes in Kalikatir Village in Kalikatir Village: Sinergi UMKM dan Inovasi Pangan: Pemanfaatan Tepung Kulit Pisang Raja Nangka dalam Pembuatan Kue Kering di Desa Kalikatir - Kurnia, Tafana Serly; Ningsih, Ika Rachman; Destiana, Evie (Journal of Empowerment and Community Service (JECSR), 2025)
Food innovation based on local ingredients is a strategy for developing Micro, Small, and Medium Enterprises (UMKM) in the food sector. Kalikatir Village has the potential to utilize waste from Raja Nangka banana peels which are rich in fiber and antioxidants to be processed into flour as raw material for cookies. This study aims to optimize the utilization of banana peel waste through training in making flour, cookie formulation, and mentoring UMKM in production and marketing. The results of the activity show that Raja Nangka banana peel flour increases the nutritional value of cookies, especially the fiber and antioxidant content. The resulting cookie products have a taste that is acceptable to consumers, a crunchy texture, and a distinctive aroma. In addition, this activity improves the skills of UMKM actors, reduces raw material costs, and opens up opportunities for diversification of local food-based products. The synergy of food innovation and UMKM empowerment contributes to increasing the added value of agricultural waste, supporting environmental sustainability, and encouraging community economic growth. Further research is needed to optimize formulations and market studies to expand the scale of production.